Analysis of the movement of an empty car on the longitudinal profile of the hill - Saidivaliev Shukhrat; Sattorov Samandar; Juraeva Diyora (E3S Web of Conferences, 2023)
At present, in the existing methods for determining the height of a hump, the height is calculated based on the most difficult conditions - winter temperature and head wind, and a four-axle empty covered wagon is selected for a poor runner. Based on the basic law of dynamics (D’Alembert’s principle) as applied to weak links and the use of analytical formulas in the article, the calculation of the kinematic parameters of the movement of cars in the braking zone of the section of the first braking position of the hump is carried out. A sorting hump 3.08 m high is considered, for a four-axle empty covered wagon the winter temperature is -100, the headwind speed is 5 m/s m. When calculating the height of the marshalling yard, it is necessary to take the technical characteristics of a four-axle empty gondola car as a poor runner, since the headwind also acts inside the gondola car and prevents the car from rolling down the hill. It is recommended to study the effect of a headwind on a four-axle empty gondola car.